Enhancement to least square-based approach for time-domain unsteady aerodynamic approximation - Ribeiro, Frederico A. [UNESP]; Dowell, Earl H.; Bueno, Douglas D. [UNESP] (My University, 2021)
The modeling of different problems in aeroelasticity requires a time-domain equation of motion, especially to design modern controllers and study nonlinear characteristics. Typically, unsteady aerodynamic forces are written in the (reduced) frequency domain and then rewritten using rational function approximations in the time domain. In this context, this Paper presents an investigation of this topic including a literature review of the Least Square method used to obtain the time-domain aeroelastic system. It discusses the physical meanings of the augmented aerodynamics states due to the lag terms. It proposes an approach to use a phase error-based index to measure the rational function approximations accuracy depending on the number of lag terms. The proposal allows the analyst to determine the number of lag parameters to establish a time-domain aeroelastic model of a specified accuracy.